Alcohol and dementia — risk or protective factor?. Issue 11 (November 2018) - Anstey, Kaarin; Peters, Ruth
A new publication from the Whitehall study confirms earlier findings that light to moderate alcohol drinkers have a reduced risk of dementia compared with abstainers and heavy drinkers. Importantly, the study follows a cohort from middle age, whereas most previous research on this topic has focused on older adults.